RANCANG BANGUN PROTOTIPE KNOWLEDGE MANAGEMENT SYSTEM BAHAN AJAR GURU DENGAN MODEL SECI DAN MVC : STUDI KASUS SDIT AL-HIKMAH CIPAYUNG DEPOK - Lestari, Ade Fitria; Sensuse, Dana Indra (LPPM Universitas Nusa Mandiri, 2014)
The ability of an educational institution in terms of science and technology became one of the very important factors. Despite those two things then it should be accompanied by qualified human resources and competitive. SDIT Al-Hikmah Cipayung Depok is an Islamic educational institution where the transfer of knowledge is still limited in the forum work meetings there has been no documentation or technology that saves teachers 'knowledge and experience in teaching. Knowledge Management System is the most effective way of tackling the problem and solution sharing and transfer of knowledge teachers at Al-Hikmah SDIT Cipayung Depok. The research method used was the establishment of the SECI model of knowledge, architectural design model application with MVC (Model-View-Controller), testing validation by Focus Group Discussion (FGD) method using a questionnaire, software testing, and black box testing and software quality testing with ISO 9126. The result of the research is a Knowledge Management System as the technology transfer of knowledge that is one of the efforts in reducing the use of paper (paperless office), making the efficiency of time, effort and cost, and better documentation management in the SDIT Al-Hikmah Cipayung Depok.